Outcome of B-Lynch Application in Patients with Post-Partum Hemorrhage Following Cesarean Section at Tertiary Care Hospital Larkana - Kainat (Indus Journal of Bioscience Research, 2025)
Background: Postpartum hemorrhage (PPH) remains a leading cause of maternal morbidity and mortality worldwide, particularly in low- and middle-income countries. Objective: This study aimed to evaluate the outcomes of B-Lynch suture application in patients with PPH following cesarean section. Methods: This prospective observational study was conducted at Shaikh Zayed Women’s Hospital, Larkana, Sindh, from 10th Oct 2024 to 10th April 2025. A total of 124 patients who developed PPH unresponsive to medical management during cesarean section were included. The B-Lynch compression suture was applied, and intraoperative, postoperative, and follow-up outcomes were recorded. Results: The mean age of patients was 29.8 ± 5.4 years, with 70.1% being multigravida. The most common risk factors were uterine overdistension (31.4%) and placenta previa/accreta (21%). The B-Lynch suture successfully controlled hemorrhage in 108 patients (87.1%), while 16 patients (12.9%) required additional interventions, including stepwise devascularization (n = 9) and hysterectomy (n = 7). The mean blood loss was 1520 ± 410 mL, and 79% required blood transfusion with an average of 2.6 units. Postoperative morbidity occurred in 16.9% of patients, with febrile morbidity being the most common. Conclusion: It is concluded that the B-Lynch compression suture is a highly effective and safe procedure for controlling PPH during cesarean section. It significantly reduces the need for hysterectomy, preserves fertility, and is associated with minimal complications, making it particularly valuable in resource-limited settings.